Sensitivity of Antenna Arrays for Long-Wavelength Radio Astronomy - Ellingson, S W (IEEE transactions on antennas and propagation, 2011)
A number of new and planned radio telescopes will consist of large arrays of low-gain antennas operating at frequencies below 300 MHz. In this frequency regime, Galactic noise can be a significant or dominant contribution to the total noise. This, combined with mutual coupling between antennas, makes it difficult to predict the sensitivity of these instruments. This paper describes a system model and procedure for estimating the system equivalent flux density (SEFD)-a useful and meaningful metric of the sensitivity of a radio telescope-that accounts for these issues. The method is applied to LWA-1, the first "station" of the Long Wavelength Array (LWA) interferometer. LWA-1 consists of 512 bowtie-type antennas within a 110 × 100 m elliptical footprint, and is designed to operate between 10 MHz and 88 MHz using receivers having noise temperature of about 250 K. It is shown that the correlation of Galactic noise between antennas significantly desensitizes the array for beam pointings which are not close to the zenith. It is also shown that considerable improvement is possible using beamforming coefficients which are designed to optimize signal-to-noise ratio under these conditions. Mutual coupling is found to play a significant role, but does not have a consistently positive or negative influence. In particular, we demonstrate that pattern multiplication (assuming the behavior of single antennas embedded in the array is the same as those same antennas by themselves) does not generate reliable estimates of SEFD.